The mediating effects of job satisfaction and organisational justice on the relationship between principals' management style and teachers' organisational citizenship behaviour: Turkey sample - Alanoglu, Muslim; Karabatak, Songul (Korean Educational Developmental Inst, 2020)
In this study, firstly the effects of cooperative and authoritarian management styles on teachers' organisational justice, job satisfaction, and OCBs were tested. Then, the mediating effects of job satisfaction and organisational justice on the relationship between principals' management style and teachers' OCBs were examined. In accordance with this aim, the prediction research design was used. The sample of the study consisted of 312 teachers. The predictive and mediating relationships between variables were examined by the structural equation model. According to the results obtained at the end of the study, both organisational justice perception and job satisfaction have partial mediating effect on the effect of cooperative management style on organisational citizenship behaviour, but neither organisational justice perception nor job satisfaction have any mediating effect on the effect of authoritarian management style on organisational citizenship behaviour.
Keywords: principals' management style; cooperative management; authoritarian management; organizational justice perception; job satisfaction; organisational citizenship behaviour